Analisis Rasio Keuangan untuk Menilai Kinerja Keuangan Perusahaan Subsektor Farmasi yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023 - Dwiki Dimas Martama; Vicky Dzaky Cahaya Putra (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the financial performance of pharmaceutical subsector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period using financial ratio analysis, particularly liquidity and solvency ratios. This research employs a quantitative approach with a descriptive method. The data used are secondary data in the form of annual financial statements of pharmaceutical companies obtained from the Indonesia Stock Exchange. Liquidity is measured using the Current Ratio (CR), solvency is proxied by the Debt to Asset Ratio (DAR), and financial performance is measured by Return on Assets (ROA). The data analysis techniques include multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results show that liquidity does not have a significant effect on the financial performance of pharmaceutical companies. In contrast, solvency has a negative and significant effect on financial performance. Simultaneously, liquidity and solvency have a significant effect on the financial performance of pharmaceutical companies listed on the IDX during the 2021–2023 period. These findings indicate that effective capital structure management and a balance between current assets and debt utilization play a crucial role in improving the profitability of pharmaceutical companies.